Peran Guru Dalam Penerapan Perilaku Hidup Bersih Dan Sehat (PHBS) Bagi AUD Di TK Lembayung Indah Kota Bengkulu - Putri, Rani Amelia; Nurwita, Syisva (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe the role of teachers in implementing clean and healthy living behaviours (PHBS) for AUD at Lembayung Indah Kindergarten in Bengkulu City. This study uses a qualitative descriptive research method. Data collection methods used in this study include observation, interviews, and documentation. The results of this study indicate that the role of teachers in implementing clean and healthy living behaviours (PHBS) for preschoolers at TK Lembayung Indah in Bengkulu City are as follows: 1) as classroom managers, teachers provide guidance on how to maintain cleanliness and health within the classroom, 2) as a facilitator, teachers provide facilities to support clean and healthy living behaviours, such as soap, sinks, trash bins, decorative plants, shoe racks, and well-maintained bathrooms at school, 3) as a mediator, teachers provide learning materials such as videos, songs, busy books, and posters, and determine the appropriate learning materials to use in the learning process, 4) As an inspirer, the teacher applies clean and healthy living behaviours (PHBS) to their students by setting an example, such as disposing of rubbish in its proper place and washing hands with soap before and after eating. 5) As an informant, the teacher provides guidance on how to use the bathroom properly and how to wash hands correctly. It can be concluded that the role of teachers in implementing clean and healthy living behaviours (PHBS) for preschoolers at Lembayung Indah Kindergarten in Bengkulu City is as follows: 1) as class managers, 2) as facilitators, 3) as mediators, 4) as inspirers, 5) as informants.